Peripheral Retinal Degenerations - K Sudhamathi; Umah Venugopal; Ajay Sharma; Deependra V Singh (Delhi Journal of Ophthalmology)
The vast array of peripheral retinal degenerations leave an ophthalmologist with numerous possible differentials and prognosticators when an individual presents to him. The following review is an aid in understanding which degenerations make retina susceptible to a possible retinal detachment in near future; and are possible indicators for prophylactic therapy at presentation and which of them do not predispose to any complications and thus can be left untreated.